Synchronization of estrus in yearling beef heifers with the MGA®/prostaglandin system: I. effect on inducement of puberty and conception rates - L.R. Corah; J.R. Yaeger; J.C. Whittier; J.C. Meiske; D.J. Patterson; K. C. Olson (Kansas Agricultural Experiment Station Research Reports, 1992)
We evaluated the estrous response and fertility of yearling beef heifers after treatment with melengestrol acetate (MGA) and prostaglandin F2" (PG). The 304 heifers, at three locations, were allotted to two treatments: nonsynchronized controls and those receiving .5 mg MGA per head daily for 14 days followed by a 25 mg PG injection 17 days after the end of MGA feeding (MGA/PG). Heifers in the control and MGA/PG groups were artificially inseminated 12 hours after observed estrus for 21 days or 6 days after PG, respectively. Conception rate at first service and overall pregnancy rate did not differ (P>.10) between MGA/PG and control heifers (64% vs. 50% and 49% vs. 38%, respectively). However, the MGA/PG system effectively induced puberty and synchronized estrus, allowing more (P<.009) heifers to become pregnant early in the breeding season (49%) compared with nonsynchronized controls that were inseminated on spontaneous estrus (14%).
Keywords: Cattlemen& #x27; s Day; 1992; Kansas Agricultural Experiment Station contribution; no. 92-407-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 651; Beef; Heifer; Puberty; MGA; Estrous synchronization